2016
DOI: 10.1128/iai.01378-15
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Resident T Cells as the Central Paradigm of Chlamydia Immunity

Abstract: bFor almost 2 decades, results from Chlamydia pathogenesis investigations have been conceptualized using a cytokine polarization narrative. Recent viral immunity studies identifying protective tissue-resident memory T cells (Trm) suggest an alternative paradigm based on localized immune networks. As Chlamydia vaccines enter the preclinical pipeline and, in the case of an attenuated trachoma vaccine, are given to human subjects, it may be useful to ask whether cytokine polarization is the appropriate framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…The oviduct dilation (g) and inflammatory infiltration (h) scores were compared between the C57BL/6J and CD8 knockout groups, and both groups of mice developed a severe oviduct pathology. nicity (37,38,45), there is no experimental evidence on whether CD4 ϩ T cells can directly promote chlamydial pathogenicity. In the current study, we have presented experimental data for filling in the gap.…”
Section: Discussionmentioning
confidence: 99%
“…The oviduct dilation (g) and inflammatory infiltration (h) scores were compared between the C57BL/6J and CD8 knockout groups, and both groups of mice developed a severe oviduct pathology. nicity (37,38,45), there is no experimental evidence on whether CD4 ϩ T cells can directly promote chlamydial pathogenicity. In the current study, we have presented experimental data for filling in the gap.…”
Section: Discussionmentioning
confidence: 99%
“…The findings on tissue-resident memory T cells have provided insight into protective immunity mechanisms to C. trachomatis infection [86]. A vaccine to prevent sexually transmitted C. trachomatis needs to develop tissue-resident memory T cells that are capable of detecting incoming C. trachomatis and mount a robust local immune response to limit the spread of infection.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%
“…The basic cellular immune responses to Salmonella and Chlamydia infection have been elucidated in mouse models and share common features (3234). As expected for intracellular bacteria, CD4 Th1 cells that express T-bet and produce IFN-γ are critical for bacterial clearance.…”
Section: Protective Immunity To Intracellular Bacteriamentioning
confidence: 99%
“…As noted above, data from parabiosis experiments have shown that nonrecirculating memory cells are critical for protective immunity using a prototype Chlamydia vaccine (49). Thus, noncirculating TRM T cells would seem to be an integral component of protective immunity to secondary infection with Chlamydia (34). Therefore, it seems likely that antibiotic treatment during Chlamydia infection will adversely affect the development of Chlamydia -specific TRM within the reproductive tract, but this issue has yet to be examined experimentally.…”
Section: Antibiotic Clearance Of Chlamydia In the Mouse Modelmentioning
confidence: 99%